The Umbilical Cord Care for Newborns at the Independent Practice of Midwife Tutik Purwani Sleman in 2022: Perawatan Tali Pusat Pada Bayi Baru Lahir di Praktik Mandiri Bidan Tutik Purwani Sleman Tahun 2022 - Khariza Fauziah; Sunarti, Nining Tunggal Sri; Kurniasari Pratiwi (Jurnal Midwifery, 2023)
Introduction Reducing neonatal mortality is very important. Neonatal mortality contributes 60% to infant mortality. One of the threats to neonates is umbilical cord infection due to umbilical cord care that is not in accordance with predetermined standards. Mrs. F is a patient who routinely checks for pregnancy at PMB Tutik Purwani, and gives birth there. Baby Mrs. F needed cord care, so open care was given to cord care. Method This research uses the case study method. Data collection was done by interview and observation. Result of the care that was carried out on baby Ny. F starts from the assessment of subjective and objective data, determines the assessment, and performs management. The midwife first performed the open method of umbilical cord care while it was still wet and fresh, with no signs of infection, at home by the grandmother and mother. At the time of the second neonatal visit, the baby’s umbilical cord had fallen off. This action is taken to prevent the baby from the dangers of umbilical cord infection which can cause neonatal death. Conclusion Open method of umbilical cord care has been carried out from assessment to evaluation properly and in accordance with midwifery care standards, characterized by the baby’s umbilical cord. F came off within four days and the wound was dry, clean, and had no signs of infection.